2017
DOI: 10.1534/genetics.117.200576
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Torso-Like Coordinates Tissue Folding During Drosophila Gastrulation

Abstract: The rapid and orderly folding of epithelial tissue during developmental processes such as gastrulation requires the precise coordination of changes in cell shape. Here, we report that the perforin-like protein Torso-like (Tsl), the key extracellular determinant for embryonic terminal patterning, also functions to control epithelial morphogenesis. We find that null mutants display a ventral cuticular hole phenotype that is independent of the loss of terminal structures, and arises as a consequence of mesoderm i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 52 publications
2
6
0
Order By: Relevance
“…All three alleles failed to undergo posterior midgut invagination in the dark, indicative of strong loss-of-function of terminal signaling (Figure S1). Blue light illumination restored tissue invagination in OptoSOS-trk and OptoSOS-Tor RNAi embryos, but not OptoSOS-tsl embryos (Figure S1), consistent with a recent report suggesting that Tsl plays an additional, terminal signaling-independent role in gastrulation (20). These preliminary experiments suggested that OptoSOS-trk and OptoSOS-Tor RNAi embryos are able to transition complete loss of terminal signaling in the dark to a strong gain-of-function phenotype upon illumination.…”
Section: Establishing Optogenetic Ras As the Sole Source Of Terminal supporting
confidence: 90%
“…All three alleles failed to undergo posterior midgut invagination in the dark, indicative of strong loss-of-function of terminal signaling (Figure S1). Blue light illumination restored tissue invagination in OptoSOS-trk and OptoSOS-Tor RNAi embryos, but not OptoSOS-tsl embryos (Figure S1), consistent with a recent report suggesting that Tsl plays an additional, terminal signaling-independent role in gastrulation (20). These preliminary experiments suggested that OptoSOS-trk and OptoSOS-Tor RNAi embryos are able to transition complete loss of terminal signaling in the dark to a strong gain-of-function phenotype upon illumination.…”
Section: Establishing Optogenetic Ras As the Sole Source Of Terminal supporting
confidence: 90%
“…In some of these species, studies have indicated that terminal patterning occurs in other ways. In Drosophila, Torso-like has other functions, including a role in dorso-ventral patterning (Mineo et al, 2017) and gastrulation (Johnson et al, 2017) The nonterminal patterning phenotypes produced in Torso-like null mutants are reminiscent of those caused by Oncopeltus RNA interference (Weisbrod et al, 2013) and over-expression of aphid torso-like in Drosophila (Duncan et al, 2013), implying these functions, rather than terminal patterning, may be more conserved.…”
Section: Terminal Patterning and Moultingmentioning
confidence: 99%
“…To generate the phm:Tsl construct, a 1.1 kb fragment of the phm promoter region (from Ono et al (2006)) was first cloned from gDNA (F -5'-CTG CAG TGA TGC GCT GCT CCT TTG T-3', R -5'-AGA TCT CAC TTT CGA TTT CCT CCT GC-3') into the pGEM-T Easy vector (Promega), before being sequenced and subcloned into pUASTattB-Tsl:eGFP (Johnson et al 2017) via PstI and BglII sites to delete the UAS sequence. Transgenic lines were made (BestGene) via ΦC31 integrase mediated transformation (Bischof et al 2007) using the ZH-51CE attP-landing site.…”
Section: Torso-like Constructs and Generation Of Transgenic Linesmentioning
confidence: 99%